2017
DOI: 10.1074/mcp.m116.061051
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Survey Indicates Sortilin as a Secondary Substrate of the ER Translocation Inhibitor Cyclotriazadisulfonamide (CADA)

Abstract: The small molecule CADA was shown to down-modulate the expression of human CD4 in a signal peptide-dependent way through inhibition of its cotranslational translocation across the ER membrane. Previous studies characterizing general glycoprotein levels and the expression of 14 different cell surface receptors showed selectivity of CADA for human CD4. Here, a PowerBlot Western Array was used as a screen to analyze the proteome of CADAtreated SUP-T1 human CD4؉ T lymphocytes. This highthroughput monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…Furthermore, the down-modulating effect of CADA seems to be selective for hCD4 and the membrane glycoprotein sortilin. As previously shown for hCD4, CADA also inhibits the co-translational translocation of sortilin in a signal peptide-dependent way [ 58 ]. The effects of CADA on sortilin were less pronounced as compared to hCD4 though, and sortilin appears to be a secondary substrate of CADA.…”
Section: Selective Inhibition Of Signal Peptide Topology Inversionsupporting
confidence: 58%
“…Furthermore, the down-modulating effect of CADA seems to be selective for hCD4 and the membrane glycoprotein sortilin. As previously shown for hCD4, CADA also inhibits the co-translational translocation of sortilin in a signal peptide-dependent way [ 58 ]. The effects of CADA on sortilin were less pronounced as compared to hCD4 though, and sortilin appears to be a secondary substrate of CADA.…”
Section: Selective Inhibition Of Signal Peptide Topology Inversionsupporting
confidence: 58%
“…Absence of this proline residue in the SP of mouse CD4 therefore implies that the alpha helix in this hydrophobic region offers a greater conformational stability that in turn might influence its interaction and positioning in the environment within the translocon. Of note, sortilin, the second substrate for CADA, holds a SP that is quite distinct from the huCD4 SP in terms of length and amino acid composition, but it contains both a glutamine and two adjacent proline residues in the hydrophobic core of its SP. It would be interesting to further examine the role of these amino acids in the sensitivity to CADA in order to deduce a putative consensus sequence for full susceptibility to CADA.…”
Section: Discussionmentioning
confidence: 99%
“…CADA does not prevent the targeting of nascent huCD4 peptides to the translocon, but instead interferes with huCD4 biosynthesis at a post‐targeting step . From a proteomic study, sortilin was recently identified as a second substrate for CADA, although with lower susceptibility to the compound as compared to huCD4 …”
Section: Introductionmentioning
confidence: 99%
“…48 The macrocyclic triamine cyclotriazadisulfonamide (CADA) is a small molecule that inhibits replication of various strains of human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) by selectively down-modulating expression of cell-surface cluster of differentiation 4 (CD4). 27,46,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] This type 1 integral transmembrane glycoprotein is expressed on immune cells and is the primary receptor required by HIV to enter host cells. CADA compounds are radically different from conventional anti-HIV agents that have viral targets and are highly susceptible to onset of resistance by mutation and selection mechanisms.…”
Section: Substrate-selective Inhibitors Of Translocationmentioning
confidence: 99%
“…A proteomic survey using high throughput monoclonal antibody panel-based immunoblotting assay of cellular signaling proteins revealed sortilin as a second substrate of CADA. 70 The screen was based on a panel of 1000 monoclonal antibodies covering a wide array of intracellular pathways. Dose-response curves are shown in Fig.…”
Section: Substrate-selective Inhibitors Of Translocationmentioning
confidence: 99%